2021
DOI: 10.1155/2021/6675208
|View full text |Cite
|
Sign up to set email alerts
|

The Role of TGF-β Signaling Pathways in Cancer and Its Potential as a Therapeutic Target

Abstract: The transforming growth factor-β (TGF-β) signaling pathway mediates various biological functions, and its dysregulation is closely related to the occurrence of malignant tumors. However, the role of TGF-β signaling in tumorigenesis and development is complex and contradictory. On the one hand, TGF-β signaling can exert antitumor effects by inhibiting proliferation or inducing apoptosis of cancer cells. On the other hand, TGF-β signaling may mediate oncogene effects by promoting metastasis, angiogenesis, and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 195 publications
(189 reference statements)
1
22
0
3
Order By: Relevance
“…TGF-β1 can suppress early-stage tumors through its potent antiproliferative activity and the induction of cell differentiation and apoptosis 65 , 66 . In advanced cancer, however, TGF-β1 actually promotes tumor invasion and metastasis by inducing the epithelial-mesenchymal transition, facilitating tumor angiogenesis, and hampering tumor immune surveillance by the host 65 67 . TGF-β1 is also implicated in many fibrotic human diseases, including pulmonary fibrosis 68 .…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β1 can suppress early-stage tumors through its potent antiproliferative activity and the induction of cell differentiation and apoptosis 65 , 66 . In advanced cancer, however, TGF-β1 actually promotes tumor invasion and metastasis by inducing the epithelial-mesenchymal transition, facilitating tumor angiogenesis, and hampering tumor immune surveillance by the host 65 67 . TGF-β1 is also implicated in many fibrotic human diseases, including pulmonary fibrosis 68 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that TGF-β and vimentin play a role in immune suppression in many human cancers and are associated with tumor dissemination, metastasis, and poor prognosis [29]. This immune suppression may be related to the tumor immune microenvironment regulated by TGF-β, indicating the importance of TGF-β as a tumor marker and possibly as a target for inhibiting the infiltration of immune cells and their toxicity to cancer cells [53]. Our results show that autocrine TGF-β1-and vimentin-mediated cytoskeleton remodeling affects the adhesion and detachment of human cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…После фосфорилирования SMAD2 и SMAD3 связываются с шаперонным белком SMAD4 и котранспортируются в ядро, где они могут регулировать экспрессию генов-мишеней TGF-β (рис. 1) [16,39,43,47].…”
unclassified
“…1. Схема сигнального пути TGF-β [47]. TGF-β стабилизирует клеточный цикл эпителиальных клеток, регулируя множественные циклин-зависимые киназы: p15, p21 и p27 каноническим путем.…”
unclassified
See 1 more Smart Citation